Protonation and Solvation Thermodynamics of Some Naphthol Derivatives in KCl Aqueous Solution of Different Ionic Strengths - Farid I. El-Dossoki (Journal of Chemistry)
The acid-base properties of naphthalen-1-ol (L1), naphthalene-1,5-diol (L2), and 4-amino-3-hydroxynaphthalene-1-sulphonic acid (L3) were characterized from pH-metric measurements in pure water and in different concentrations (0–4 mol kg−1) of aqueous KCl solutions at the temperature range of T = (293.15 to 213.15) K at 5 K intervals. The results reveal that naphthalen-1-ol and naphthalene-1,5-diol molecules have two ionisable protons (of the hydroxyl groups) while 4-amino-3-hydroxynaphthalene-1-sulphonic acid has three ionisable protons (hydrogen ion of the hydroxyl group, SO3H, and NH3+). Modeling of the data was done by applying Debye-Hückel model. The protonation and the solvation processes of all studied ligands are spontaneous and endothermic processes. Also the solubilities of naphthalen-1-ol, naphthalene-1,5-diol, and 4-amino-3-hydroxynaphthalene-1-sulphonic acid were determined. The data were analyzed using Setschenow equation and the values of Setschenow coefficients (km) were determined. From the solubility data, the activity coefficients were obtained. The values of the total solubilities (ST) for naphthalen-1-ol and naphthalene-1,5-diol were found equal to the values of their neutral species (S0). On the other hand, the total solubility for 4-amino-3-hydroxynaphthalene-1-sulphonic acid is different from that of its neutral species. The results also indicate solubility decrease in pure water from L1-L2-L3.